Analysis of the impact of landslides on rural community livelihood in Rwanda: Case of Ngororero district - Claudine, Ihorikiza Marie; Ndokoye, Pancras (International Journal of Geography and Geology, 2023)
The study entitled “Analysis of the impact of landslides on rural community livelihood in Rwanda. Case of Ngororero District” was conducted to analyze the impact of landslides on rural community livelihood in Rwanda, a case of Ngororero District. The study objectives were to: Delineate landslides endangered areas and identify the causes, evaluate rural community livelihood status in Ngororero district throughout the study (2016-2020), and analyze the impact of landslides on rural community livelihood in Ngororero District. The study targeted 19,999 households as the study population; from the three sectors of the Ngororero district namely, Muhanda, Kavumu, and Sovu sectors. A sample of 392 members from that population was selected purposively. Data collection tools and techniques used to obtain primary and secondary data were interviews, questionnaires, observation, and documentation. The study was survey in nature and used qualitative, quantitative, and correlative research designs. Data analysis and map production were done using SPSS 16.0, and Geographic Information System (GIS) 10.8 software. The study findings confirm that the landslides occurrence had a significant impact on community members’ livelihood in Ngororero District, such as deaths and injuries of community members, income reduction, food insecurity problems, displacements and houses destruction. It is recommended that the government manages the situation and keeps it in control so that both government and the citizens use appropriate and durable materials in the construction of houses and infrastructures like roads, classrooms, and health centers to avoid potential damage due to landslide occurrence.